2015
DOI: 10.1038/srep15082
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise evolution of pandrug-resistance in Klebsiella pneumoniae

Abstract: Carbapenem resistant Enterobacteriaceae (CRE) pose an urgent risk to global human health. CRE that are non-susceptible to all commercially available antibiotics threaten to return us to the pre-antibiotic era. Using Single Molecule Real Time (SMRT) sequencing we determined the complete genome of a pandrug-resistant Klebsiella pneumoniae isolate, representing the first complete genome sequence of CRE resistant to all commercially available antibiotics. The precise location of acquired antibiotic resistance elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 63 publications
0
123
0
Order By: Relevance
“…2C) (15), KPNIH33 carries two chromosomal bla KPC-3 copies with Tn4401b (14,15), and MS6671 carries three chromosomal bla OXA-181 copies with ISEcp1 (Fig. 1B) (22). We describe that the CN1 chromosome carries three bla CTX-M-15 copies with ISEcp1 and one bla KPC-2 copy with Tn4401a.…”
Section: Discussionmentioning
confidence: 98%
“…2C) (15), KPNIH33 carries two chromosomal bla KPC-3 copies with Tn4401b (14,15), and MS6671 carries three chromosomal bla OXA-181 copies with ISEcp1 (Fig. 1B) (22). We describe that the CN1 chromosome carries three bla CTX-M-15 copies with ISEcp1 and one bla KPC-2 copy with Tn4401a.…”
Section: Discussionmentioning
confidence: 98%
“…Insertional inactivation caused by diverse insertion sequences (IS), belonging to several families and inserted at different locations within the mgrB gene, is often responsible for acquired resistance to colistin in K. pneumoniae (105,117,120,(130)(131)(132) and Klebsiella oxytoca (133,134). Recently, the transposition of genes encoding extended-spectrum ␤-lactamases (ESBLs) or carbapenemases, leading to disruption of the chromosomal mgrB gene, was reported as a source of resistance to colistin (135,136). Notably, selective pressure with ␤-lactams leading to the acquisition of ␤-lactamase genes may therefore be responsible for coselection of colistin resistance.…”
Section: Regulators Of the Pmrab And Phopq Two-component Systemsmentioning
confidence: 99%
“…Similarly, it has been suggested ISKpn25 is involved in DNA rearrangements among pKpQIL-like and possibly other plasmids (11). An additional study showed that a mobile element containing the carbapenemase OXA-181 disrupted the mgrB gene in a carbapenem-and colistin-resistant K. pneumoniae isolate from a patient from the United Arab Emirates (12). In the same isolate, a copy of a second element harboring CTX-M-15 (ISEcp1-bla CTX-M-15 ) was inserted into ompK35, inactivating the gene.…”
mentioning
confidence: 99%